An economic model for the use of yoghurt in type 2 diabetes risk reduction in the UK. Issue 1 (December 2016) - Lenoir-Wijnkoop, Irene; Mahon, James; Claxton, Lindsay; Wooding, Alicia; Prentice, Andrew; Finer, Nick
Abstract Background In the UK, diabetes accounts for approximately 10% of the total UK National Health Service (NHS) resource expenditure, a figure that has been predicted to increase to 17% by 2035/2036. Meta-analysis of association studies indicate that yogurt consumption is potentially protective against type 2 diabetes (T2D). The purpose of this study was to explore the potential economic benefit to the UK NHS of a population increase in yoghurt consumption as a preventative measure against development of T2D. Methods A patient simulation model was constructed for adults in the UK over the age of 25 years old using incidence rates for developing T2D with both current and increased yoghurt consumption. The reduction in risk in developing T2D associated with higher yoghurt consumption was taken from a meta-analysis of studies of dairy consumption on T2D risk. In each annual cycle of the model a patient could develop complications and comorbidities that are known to be more common in patients with T2D. Incidence rates for these conditions for diabetics and non-diabetics were taken from published studies. The model had a 25 year time horizon. Results The model predicts that increasing average yoghurt consumption by adults over 25 years of age in the UK by 100g daily could result in 388, 000 fewer people developing T2D over 25 years. This could save the UK NHS £2.3bn in direct T2D treatment costs and the costs of treating T2D associated complications. In addition, 267, 000 QALYs would be generated. If the NHS values a QALY valued at £20, 000, this would mean that the NHS should be prepared to pay £5.5bn for an intervention that generated the same number of QALYs. Conclusions Increasing yoghurt consumption in the adult population of the UK by 100g per day could generate substantial cost savings to the NHS as well as significant patient benefit through reductions in the incidence of T2D.